2017
DOI: 10.1016/j.ymthe.2016.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Specific and Efficient Regression of Cancers Harboring KRAS Mutation by Targeted RNA Replacement

Abstract: Mutations in the KRAS gene, which persistently activate RAS function, are most frequently found in many types of human cancers. Here, we proposed and verified a new approach against cancers harboring the KRAS mutation with high cancer selectivity and efficient anti-cancer effects based on targeted RNA replacement. To this end, trans-splicing ribozymes from Tetrahymena group I intron were developed, which can specifically target and reprogram the mutant KRAS G12V transcript to induce therapeutic gene activity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…To solve this problem and improve the therapeutic potential of this approach, safer, more efficient, and endogenously and exogenously regulated trans ‐splicing ribozymes are required (Figure ). Improvement of specificity of intracellular trans ‐splicing reaction and no off‐target effects were reported through 5′‐end rapid amplification of cDNA ends (RACE) PCR analysis of the total trans ‐spliced products in the target RNA‐expressing cells by the modification of ribozyme to contain EGS upstream of IGS and the P10 helix sequence (Jung & Lee, ; Kim et al, ; Kim et al, ; Kwon et al, ). Moreover, recent studies have reported the development of trans ‐splicing ribozymes for which the activities can be precisely regulated using endogenous circumstances (Kim & Lee, ) or tissue‐specific miRNAs (Kim et al, ; Won et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To solve this problem and improve the therapeutic potential of this approach, safer, more efficient, and endogenously and exogenously regulated trans ‐splicing ribozymes are required (Figure ). Improvement of specificity of intracellular trans ‐splicing reaction and no off‐target effects were reported through 5′‐end rapid amplification of cDNA ends (RACE) PCR analysis of the total trans ‐spliced products in the target RNA‐expressing cells by the modification of ribozyme to contain EGS upstream of IGS and the P10 helix sequence (Jung & Lee, ; Kim et al, ; Kim et al, ; Kwon et al, ). Moreover, recent studies have reported the development of trans ‐splicing ribozymes for which the activities can be precisely regulated using endogenous circumstances (Kim & Lee, ) or tissue‐specific miRNAs (Kim et al, ; Won et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in contrast to ASO‐ and siRNA‐based approaches and genome editing approaches, trans ‐splicing ribozyme would not require any kinds of endogenous and/or exogenous proteins that could induce cellular toxicity and potential immunogenicity, and control of target binding length or post‐transcriptional regulation could increase the ribozyme specificity and thus minimize off‐target effects. Because of this RNA editing ability, trans ‐splicing ribozymes have played an important role in the fields of gene therapy (Ban et al, ; Byun, Lan, Long, & Sullenger, ; Carter et al, ; Jung, Kwon, & Lee, ; Kastanos, Hjiantoniou, & Phylactou, ; Kim, Kim, Yang, Jeong, & Lee, ; Kwon et al, ; Phylactou, Darrah, & Wood, ; Rogers, Vanoye, Sullenger, & George, ; Ryu, Kim, & Lee, ; Shin, Sullenger, & Lee, ; Song & Lee, ; Won & Lee, ) and molecular imaging (Hong et al, ; Kim et al, ; Kim et al, ; So, Gowrishankar, Hasegawa, Chung, & Rao, ). In this review, we will describe trans ‐splicing ribozymes, particularly the group I intron‐derived types, as well as gene therapy applications.…”
Section: Introductionmentioning
confidence: 99%
“…In malignancies and pathological tissue induction, where multiple pathways are dysregulated, repairing a single gene may not be sufficiently effective and hence require expression of multiple therapeutic genes. Trans -splicing ribozymes with reprogramming capabilities have been developed that not only remove viral transcripts and tumor-related genes but also induce cell death leading to elimination of virus-infected and cancer cells (Won and Lee, 2012; Carter et al, 2014; Kim et al, 2017). Since reprogramming genes comes with a great risk of unconstrained expression and unintended gene removal, it is paramount to introduce elements that maintain a check on the activity of trans -splicing ribozymes.…”
Section: Spectrum Of Nucleic Acids For Clinical Utilitymentioning
confidence: 99%
“…This specific trans-splicing reaction with the ability of discrimination target RNA from non-target one, even with a single nucleotide difference, makes it as an attractive novel treatment strategy for KRAS point mutations. Regarding KRAS -G12V mutation as one of the most prevalent point mutation, Tetra hymena group I intron-based trans-splicing ribozyme designed for selective cleavage of KRAS -G12V transcript 195 . An accurate and specific intracellular trans-splicing reaction of the designed ribozyme systems with the KRAS -G12V target RNA, leads to efficient reduction of transcript level.…”
Section: Other Approachesmentioning
confidence: 99%
“…Except that replacement of RNA, concurrent induction of suicide gene activity resulting in cytotoxicity and effective retardation of cancer cells harboring KRAS mutation 196 . Moreover, trans-splicing and therapeutic anti-cancer gene activity was selectively and efficiently induced only in KRAS -mutant cancer cells without targeting of cells expressing wild-type KRAS 195 . …”
Section: Other Approachesmentioning
confidence: 99%